Dream Factories of a Former Colony: American Fantasies, Philippine Cinema - Capino, José B. (University of Minnesota Press, 2010)
By tracking American fantasies in Philippine movies from the postindependence period to the present, José B. Capino offers an innovative account of cinema’s cultural work in decolonization and globalization. Through close readings of more than twenty Philippine movies, Capino demonstrates the postcolonial imagination’s vital role in generating pragmatic and utopian visions of living with empire.